2005
DOI: 10.1007/11422778_56
|View full text |Cite
|
Sign up to set email alerts
|

An Approximate Queueing Model for Limited-Range Wavelength Conversion in an OBS Switch

Abstract: We develop an analytical model for modeling limited-range wavelength conversion employed in an OBS switch. The system is modeled as a simultaneous resource possession problem. We propose a productform solution which calculates approximate blocking probabilities for degree of conversion d = 1, 2 and for large number of wavelengths. We then propose an approximate model for large values of d. The output of our model was verified with simulation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The asynchronous bufferless switches with LRWC were investigated [7] analytically for smaller conversion ranges and a small number of wavelengths, while they were investigated approximately for larger conversion ranges and a large number of wavelengths. An approximate method named as overflow fixed point (OFP) was proposed to calculate blocking probability of an asynchronous bufferless OBS switch with sufficient number of LRWCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The asynchronous bufferless switches with LRWC were investigated [7] analytically for smaller conversion ranges and a small number of wavelengths, while they were investigated approximately for larger conversion ranges and a large number of wavelengths. An approximate method named as overflow fixed point (OFP) was proposed to calculate blocking probability of an asynchronous bufferless OBS switch with sufficient number of LRWCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the connection request may be refused at an intermediate OXC, which will cause the burst to be lost. It has been demonstrated that in order to keep the burst loss rate within acceptable levels, the per wavelength utilization has to be very low [10]. Burst loss is a characteristic that we would like to avoid especially in high QoS demanding e-science applications such as particle physics [12].…”
Section: Introductionmentioning
confidence: 99%
“…In limited range wavelength conversion, a packet arriving on a wavelength can be converted to a fixed set of wavelengths above and below the original wavelength. Such converters are called Limited Range TWCs (LR-TWC) [4]. For LRTWCs, conversion degree d is defined as the total number of wavelengths available on both sides of the original wavelength for conversion purposes.…”
Section: Introductionmentioning
confidence: 99%